Takaful in Market Reality: A Critical Assessment of Its Distinction from Conventional Insurance - Muhammad Luthfi Mohammad Masruh; Mohd Aizul Yaakob; Mohamad Hafiz Darpen; Syahruddin Sumardi (Lembaga Yasin AlSys, 2026)
This paper critically examines the distinction between takaful and conventional insurance through the lens of maqasid al-Shari’ah. While existing scholarship has often compared the two systems primarily in terms of contractual structures and institutional arrangements, this study argues that contemporary takaful practices frequently replicate conventional insurance models, thereby raising concerns regarding their substantive alignment with Islamic principles. Methodologically, the paper adopts a qualitative doctrinal approach using content analysis of academic literature, fatwa positions, and regulatory guidelines. The analysis demonstrates that the fundamental distinction between takaful and conventional insurance lies not merely in structural modification, but in the ethical foundations of mutuality, justice, and risk-sharing that takaful is intended to uphold. The findings indicate that operational pressures and market realities have weakened these ideals, resulting in persistent challenges related to governance, surplus management, and product design. By incorporating maqasid considerations, particularly hifz al-māl and ʿadl, the study reorients the discourse on takaful from a narrow compliance-based perspective toward a more value-driven framework. The paper concludes that preserving the distinct identity of takaful requires moving beyond formal legal compliance to ensure that its operations genuinely reflect the higher objectives of Shari’ah. This study contributes theoretically by enriching the Islamic finance literature through a maqasid-centric perspective and offers practical implications for regulators, takaful operators, and policymakers seeking to realign industry practice with its original ethical foundations.